NUMERICAL SIMULATION OF SLUMP FLOW TEST OF CEMENT PASTE COMPOSITES - Jiří Němeček; Jiří Němeček (Acta Polytechnica CTU Proceedings, 2021)
This study presents a numerical simulation of the mini-slump flow test performed on the Haegerman table, according to EN 1015-3. The two-dimensional axisymmetrical Volume of fluid (VOF) model is used for the calculation. Various scenarios with the different model set up and boundary conditions were calculated to show how the results are affected. Simulations with different lifting velocities were carried out and compared to the case with instantaneous demolding, which is commonly used in numerical simulations. Also, the effect on results is shown between noslip and specific shear boundary conditions on the mold. The results of simulations indicate that mold lifting should be considered in numerical modeling even if calculation time is highly prolonged. Lifting velocities should not exceed the value of 0.2 m/s in order to maintain laminar flow and stable calculation.